1987
DOI: 10.1007/bf01244347
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of monoamine neurotransmitters in the evolution of infarction in ischemic striatum

Abstract: The time course of changes in monoamine metabolism in ischemic striatum was assessed by measurement of levels of dopamine (DA), dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA), serotonin (5-HT) and 5-hydroxy-indole-acetic acid (5-HIAA) 2, 4, 7 and 16 hours after irreversible unilateral carotid ligation in Mongolian gerbils with stroke. DA was reduced to 30% of the level in the contralateral non-ischemic striata by 2 hours after stroke, but DOPAC was significantly elevated (p less than 0.01) to 227%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…due to failure ofDA reuptake mechanisms or ischemia-induced metabolic enzyme failure). However, several previous studies have demonstrated increased whole tissue levels of HVA and DOPAC following stroke in gerbils (see Weinberger and Nieves-Rosa, 1987). It appears, therefore, that catecholamine metabolism does proceed following ischemia but that the HVA and DOPAC formed remain within the metabolizing cells and thus are not monitored by the dialysis technique.…”
Section: Discussionmentioning
confidence: 95%
“…due to failure ofDA reuptake mechanisms or ischemia-induced metabolic enzyme failure). However, several previous studies have demonstrated increased whole tissue levels of HVA and DOPAC following stroke in gerbils (see Weinberger and Nieves-Rosa, 1987). It appears, therefore, that catecholamine metabolism does proceed following ischemia but that the HVA and DOPAC formed remain within the metabolizing cells and thus are not monitored by the dialysis technique.…”
Section: Discussionmentioning
confidence: 95%
“…Additional evidence of continued metabolism is the fact that dopamine nerve terminals isolated from the ischemic cerebrum can actively take up dopamine in vitro for up to 8 hours after ischemia (Weinberger and Nieves-Rosa, 1987). Tissue levels of the dopamine metabolites, DOPAC and HVA are also elevated for up to 7 hours after ischemia -additional evidence that dopamine metabolism continues during tissue ischemia (Weinberger and Nieves-Rosa, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…C A D F in the ischemic striatum is not seen uniformly throughout the neuropil and varies from region to region in time. This accounts for the continued presence of C A D F even though levels of CA fall precipitously to 25% to 30% of control in both the ischemic cerebral hemisphere (Lavyne et al, 1975;Lust et al, 1975;Mrsulja et al, 1976;Zervas et al, 1974) and striatum (Zervas et al, 1974;Weinberger and Nieves-Rosa, 1987) within two hous after stroke, probably secondary to acute release of CA from nerve terminals (Lavyne et al, 1975;Meyer et al, 1974;Brannan et al, 1987). Studies of striatal D A release in vivo with electrochemical detection have shown that there is acute massive release of DA, corresponding to depletion of visible CADF in the striatum 2 hours after stroke (Ahagon et al, 1980).…”
Section: Discussionmentioning
confidence: 95%